The victim : a novel - Bellow, Saul. (New York, NY : Penguin Books, 1996)
"Asa Leventhal ... is accosted in a park near his home by a down-at-the-heels stranger who accuses him of ruining his life ... Leventhal gradually succumbs to the man's story and comes to believe that he has, in fact, caused the man irreparable damage ... [he] descends into a nightmare of paranoia and fear"--P. [4] of cover.
Keywords: New York (N.Y.) -- Fiction